In situ observation of gating phenomena in the flexible porous coordination polymer Zn2(BPnDC)2(bpy) (SNU-9) in a combined diffraction and gas adsorption experiment - Bon, Volodymyr; Senkovska, Irena; Wallacher, Dirk; Toebbens, Daniel M.; Zizak, Ivo; Feyerherm, Ralf; Mueller, Uwe; Kaskel, Stefan (Inorganic Chemistry, 2014)
The intrinsic structural dynamic during the adsorption of CO2 at 195 K and N2 at 77 K on flexible porous coordination polymer Zn 2(BPnDC)2(bpy) (SNU-9) was studied in situ by powder XRD. The crystal structures of as made and solvent free (activated) phases were determined by single crystal X-ray diffraction. During the structural transformation caused by activation, the rearrangement of Zn-O bonds occurs that leads to changes in coordination environment of Zn atoms. Such changes lead to the contraction of the unit cell and to decreasing unit cell volume of nearly 28% in comparison to the pristine as made structure. The solvent accessible volume of the unit cell decreases from 40.8% to 12.8%. The adsorption of CO 2 and N2 on SNU-9 proceeds in a different way: the formation of intermediate phase during the CO2 adsorption could be postulated, while the transformation from narrow pore form to the open structure occurs in quasi-one-step in the case of N2 adsorption (the intermediate phase is formed only in very narrow pressure region). The transformation of the structure is guest dependent and the differences in the structures of CO2@SNU-9 at 195 K and N2@SNU-9 at 77 K were proven by Pawley and Rietveld refinements of powder XRD patterns. The structure of N2@SNU-9 is identical to this of as synthesized phase, while the structure of CO2@SNU-9 differs slightly. © 2014 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20